2013
DOI: 10.1126/scitranslmed.3005166
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Remissions of Severe Pemphigus After Rituximab Therapy Are Associated with Prolonged Failure of Desmoglein B Cell Response

Abstract: Pemphigus is a severe blistering condition of the skin and mucosa caused by autoantibodies directed against desmogleins, which are a type of keratinocyte adhesion protein. B cell depletion by rituximab has short-term efficacy against pemphigus. We aimed to assess the long-term course of pemphigus patients after B cell depletion and to understand the immunological mechanisms that mediate long-lasting remissions. We evaluated the clinical course of 22 pemphigus patients treated with rituximab after a 79-month me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
201
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 211 publications
(227 citation statements)
references
References 40 publications
16
201
0
10
Order By: Relevance
“…This finding is in line with previous studies in rheumatoid arthritis which showed that serum IgG titers against pathogens such as pneumococcal capsular polysaccharides or TT were not significantly affected by rituximab (43). The dramatic inhibitory effect of rituximab on anti-Dsg3 IgG serum levels strongly suggests that their secretion largely depends on short-lived autoreactive plasma cells (44). Moreover, Dsg3-specific IgG-producing B cells were detected in PV patients by ELISPOT assay upon ex vivo stimulation of their peripheral lymphocytes with Dsg3 (45).…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with previous studies in rheumatoid arthritis which showed that serum IgG titers against pathogens such as pneumococcal capsular polysaccharides or TT were not significantly affected by rituximab (43). The dramatic inhibitory effect of rituximab on anti-Dsg3 IgG serum levels strongly suggests that their secretion largely depends on short-lived autoreactive plasma cells (44). Moreover, Dsg3-specific IgG-producing B cells were detected in PV patients by ELISPOT assay upon ex vivo stimulation of their peripheral lymphocytes with Dsg3 (45).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Colliou et al reported a 77% relapse rate, comparable to our study, after a median 79-month follow-up period. 17 Taken together, we can suggest that a single cycle of rituximab may not achieve a long-standing remission for pemphigus.…”
Section: Discussionmentioning
confidence: 85%
“…hi B cells and IL-10 production compared with untreated patients or patients not responding to therapy (53). It is possible that Bregs may contribute to restoration of tolerance in rituximabresponsive pemphigus patients.…”
Section: Role In Diseasementioning
confidence: 99%